Proposed method for enhancing quantum bit error rate using quantum key distribution technique - Abubakar, M.Y. (Institute of Electrical and Electronics Engineers Inc., 2014)
The current public key infrastructure (pki) encryption/decryption methods are still vulnerable to attacks. The main issue is, the public key algorithm suffers no effective solutions which are natural within particular integer factorization, distinct logarithm and also elliptic curve interactions. It might be computationally possible for an individual to create public and private key set computationally for attacking purposes. The current single channel quantum key distribution (qkd) technique suffers high quantum bit error rates (qber) in the presence of eavesdropping attacks. Therefore this high error rate needs to be reduced for better security using two channels qkd. With the current emergence of quantum computers many security algorithm that could take classical computer years to break could now be broken in matter of seconds. Therefore stronger quantum cryptography is needed for high security networking. This paper is proposed to provide a way for solving the key transmission issues using qkd, as a new method, by providing two quantum channels to improve qber. In addition also to develop an algorithm for integrating pki and qkd in solving the secrete key sharing issues in grid environment. The research methodology will require the use of qkd devices to be placed at the end of the sender and the receiver nodes for quantum channel secrete key sharing. The outcome of the research shall provide highly enhanced network cryptography mechanism for cyber security. Â© 2014 IEEE.